ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS HASIL KERJA AUDITOR INTERNAL DAN EKSTERNAL - Dian Kurniasari (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
This study examines ethical orientation, professional commitment, audit experience, job satisfaction and motivation on the quality of auditor work. The research data was obtained from internal and external auditorsin Semarang. Sampling was done by convenience sampling method, conducted in Hananta Budianto & Rekan KAP and two private companies namely Ernst & Young and Formula Land, and PT. Pertamina as BUMN. The auditor group examined included both internal and external auditors. The results show ethical orientation, professional commitment, audit experience, job satisfaction and motivation have a positive effect on thequality of auditor work. Auditor job satisfaction has the greatest influence on the quality of the Auditor's work. Auditor satisfaction can also increase if work can be completed on time, work-related compensation, and a supportive work environment. The results of this study can motivate interested parties to be able to give awards for certain achievements and opportunities for a better career as an auditor professionalism.